KEMAMPUAN PEDAGOGICAL CONTENT KNOWLEDGE (PCK) CALON GURU BIOLOGI FKIP UMS DALAM PENYUSUNAN RPP KURIKULUM 2013 TAHUN AKADEMIK 2016/2017 - Adi, Ayu Septiyani, Dra. Hariyatmi, M. Si (2017)
Teachers hold a major role in determining the success of the process and the results of the study are either the same as the teacher candidate must have the ability of Pedagogical Content Knowledge (PCK). The purpose of the study to find out the capabilities of the PCK prospective teachers of biology PEDAGOGY curriculum in preparing the lesson plan teacher of biology pedagogy UMS 2013 school academic 2016/2017. Type a descriptive qualitative research with strategy in the form of case studies. Research methods used to obtain data documentation CK, PK and PCK, data analysis techniques are used that is descriptive. The population in this research is the entire lesson plan curriculum 2013 artificial biology teacher student candidate 2013 teacher of biology pedagogy UMS on internship activities assistant teachers 2016. The results showed the ability of PCK has a very good percentage (89.41%). Based on the results can be concluded that the ability of PCK candidate teacher of biology pedagogy UMS including very good.